The Implementation Of Genre-Based Approach In English Teaching At kejar Paket C Program Of SKB Surabaya (An Ethnography Study) - Winarti, Winarti (2012)
The object of this research is the teaching learning process of English adopting Genre-based Approach. The writer describes the process of teaching English adopting Genre-based Approach in Kejar Paket C program of SKB Surakarta. The objective of the study is to describe the learning objective of Genre-based Approach for teaching of English at Kejar Paket C program in SKB Surakarta, describe the syllabus used in Genre-based Approach, describe the material used in Genre-based Approach, describe the procedure in teaching English using Genre-based Approach. This is an ethnography study. The writer uses the Ethnography research in order to make a systematic and accurate description concerning with the teaching of English in Kejar Paket C program of SKB Surakarta. The method of collecting data is interview, document, and observation. The data in this research are analyzed by using descriptive qualitative analysis. The results of the study are as follows. The procedure used by the teacher is appropriate with theory of genre. There are two patterns; BKOF-MOT-JCOTICOT and BKOF-MOT-ICOT. This research also shows the kinds of classroom activities in each stage. In BKOF, the activities are asking questions and giving explanation; giving model of text is the activity in MOT; in JCOT, the activity is making group in doing activities; giving the task for homework in ICOT.